PENGARUH LUAS LAHAN TERHADAP PENDAPATAN PETANI KARET DI DESA PULAU INGU KPECAMATAN BENAI KABUPATEN KUANTAN SINGINGI - Desi Gustina Desi Gustina; Rina Selva Johan Rina Selva Johan; Riadi Armas Riadi Armas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This Result aims to determine the effect on the performance of the farm to earnings of farmer of  rubbers Country side of  Island of Ingu of Sub district of  Benai of  Regency of Pestle Singingi. This  Research in Country side of Island of Ingu from August 2014 till finish. Method of Research used quantitative descriptive method. Population is all farmer of rubber Country side of Island of  Ingu as much 60 responder which is selecting as a sample. Data collection instrument used was a questionnaire and data analysis with model of simple linear regression. Result of this research indicate that wide farm have an effect on signifikan to earnings of farmer of rubbers Countryside of Island of Ingu of Subdistrict of Benai of Regency of  Pestle Singingi. This Matter seen from result test simple linear  regression with level of signifikan 5% obtained a f value to wide of  farm < 1 Ha F-hitung > F-tabel ( F-Hitung 1894.013 > F-Tabel 4,10) evidence indicating that F-hitung > Wide F-tabel  farm have an effect on to earnings of farmer of  rubber  equal to 98,0%, to  wide of  farm 1-2 Ha Fhitung > Ftabel ( F-Hitung 141.963 > F-Tabel 4,75) wide variable farm to earnings equal to 93,4%, to wide farm > 2 Ha F-hitung > F-tabel ( F-Hitung 442.300 > F-Tabel 5,99) influence of wide variable  farm to earnings equal to 98,4 Key words : Wide  Farm, Earnings